Energy growth nexus - RAGATOA, Dissirama Bagnaguim (KDI School, 2020)
Mainstream economics doesn’t give much importance to energy but, there is no doubt about the contribution of energy to economic activities. This paper looks at the causal effect of electricity on economic in the energy growth nexus in West Africa. We use ARDL bounds test to test for cointegration and Granger causality to identify the causality direction and finally an instrumental variable regression to estimate the causal effect of electricity on economic growth. The ARDL bounds test shows no cointegration between electricity use and economic growth. The Granger causality based on Vector Autoregression model shows a unidirectional relationship from electricity to GDP in Benin and from GDP to electricity use in Ghana and Senegal. However the test shows bidirectional causality in Togo and Nigeria. The causal effect based on instrumental variable approach shows that a 1% in electricity use per capita yields 0.17% increase in per capita income.
Thesis(Master) -- KDI School: Master of Development Policy, 2020
Keywords: Energy consumption--Africa, West; Energy policy--Africa, West